THE USE OF TPR STORYTELLING IN TEACHING ENGLISH VOCABULARY - Herni Juharno, - (2010)
This study is a quasi-experimental study which examines the effectiveness of TPR storytelling in teaching English vocabulary. The study employed non-equivalent control group design. The sample was 30 fourth-grade students of SDN Raya Barat II, in Bandung which was selected by using purposive sampling. For its framework for analysis, this study implemented quantitative approach to answer the research question. Vocabularies pre-test and post-test were employed to obtain the data. The data were then analyzed by using paired simple t-test on SPSS 16.0 for windows program and the calculation of effect size. The study showed that the implementation of TPR storytelling during teaching program was quite successful, despite some limitation. The quantitative data showed the improvement of student's vocabulary mastery. There is an improvement on students' vocabulary test score after the implementation of TPR storytelling. The paired simple t-test (- tobtain < - tcritical and + tobtain > tcritical (-8.547 < -2.045 and 8.547 > 2.045) and p value are lower than 0.05 (0.000 < 0.05). It showed a significant difference between the pre-test mean value and post-test mean value of the class. In addition, the effectiveness of TPR storytelling method was supported with a large effect size (r = 0.518). Although some difficulties were faced by the students in teaching program, such as the use of English in communication, TPR storytelling motivated them to get involved actively in the learning process. Therefore, based on the findings, it is recommended TPR storytelling to be implemented during English teaching and learning process in elementary school in order to improve students' vocabulary mastery. It is also important for teacher to select appropriate stories and actions with the students' needs, interests, and curriculum as well.